The Correlation between Hemoglobin Levels and Physical Fitness in Teenage Taekwondo Athletes - Nur Istiqomah, Isnanda Putri; Kristiyanto, Agus; Ardyanto, TonangDwi (International Journal of Human and Health Sciences (IJHHS), 2022)
Background:Taekwondo is a sport which focused on endurance and strengths. In a taekwondo competition, an athlete with low level of physical fitness can cause fatigue due to decreased concentration in athletes during the match and will affectthe athlete’s performance. One of factor which affect the physical fitness of athletes is hemoglobin levels. Low hemoglobin levels in athletes will inflict sports anemia because of lacking of oxygen binding ability and will interfere the oxygen transportation in every part of the cells inside the body. Objective: this study analyze the correlation between hemoglobin levels with physical fitness in teenage taekwondo athletes. Material and Methods: the study was used cross sectional design. The total of samples were 61 respondents and samples randomly selected. The data had collected which hemoglobin levels use cynameth blood test and physical fitness data using MFT (multistage fitness test) running test. Data analysis conducted by using bivariateanalysislike Spearman rank correlation test. Result and Discussion: the result has showed, there is a correlation between hemoglobin levels and physical fitness in taekwondo athletes for teenagers (p=00,27). The r value is 0,431 meansindicatethe strengthofcorrelationbetweenvariablesispositive. Conclusion: there is a correlation between hemoglobin levels and physical fitness in teenage taekwondo athletes. International Journal of Human and Health Sciences Vol. 06 No. 02 April’22 Page: 204-207